BLAST LUNG INJURY: OUR EXPERIENCE AT A TERTIARY CARE MILITARY HOSPITAL - Burki, Ahmed Mujadid; Mahboob, Saira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the management and mortality in patients with blast lung injury at a tertiary care military hospital.Study Design: Prospective, observational study.Place and Duration of Study: Intensive Care Unit, Combined Military Hospital, Peshawar, from Jan 2013 to Dec 2014.Methodology: After approval from Hospital Ethics Committee, 38 patients diagnosed with blast lung injury who were admitted to intensive care unit were included in our study.Results: The mean age was 29.68 ± 4.3 years and all the patients were male. The incidence of blast lung injury in trauma patients was 38 (10.2%). Most of the patients 18 (47.4%) had severe ARDS due to blast wave and most of the patients 28 (73.6%) required mechanical ventilation with lung protective strategy. The mortality in patients diagnosed with blast lung injury was 2 (5.2%).Conclusion: Blast lung injury is a common complication in survivors of bomb blast. As military doctors who treat both armed forces as well civilian casualties from blast injuries; the physician treating blast injury should be conscious of risk of patient developing blast lung injury; so that early recognition and prompt management with lung protective strategy can prevent increased morbidity and mortality.